Optimalisasi Desain Penerangan Jalan Umum (PJU) Akses Gudang PT Petrokimia Gresik Dengan Metode Fuzzy Logic - Muchammad Galih Wibisono; Denny Irawan (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2025)
This study aims to analyze the planning of Public Street Lighting (PJU) using the fuzzy logic method according to the SNI 7391:2008 standard, which stipulates the technical requirements for street lighting to ensure the safety and comfort of users. The existing design of PJU is known to be less than optimal in terms of energy efficiency and cost, with an excessive number of lamps and ineffective arrangements. The fuzzy logic model is designed to overcome this problem, with input parameters including road length, road width, and lamp power, while the output includes the distance between lamp poles, the height of the lamp pole, and the number of lamps required. This model is developed and simulated using MATLAB with a zigzag lamp installation approach on the right and left sides of the road. The simulation results show that this method produces a more optimal design, meets the SNI 7391:2008 standard, while offering a more efficient and effective solution than the existing design. By reducing the number of lamps from 46 to 21 units, power consumption and investment costs have been optimized without sacrificing lighting quality. This study makes a significant contribution to the development of a smart technology-based street lighting system, which not only meets technical standards but also supports sustainability and operational efficiency.   Keywords— Fuzzy Logic, MATLAB, Public Street Lighting, PJU Planning, SNI 7391:2008